Hierarchical microstructure design for strength-toughness optimization of 700 MPa steel rebars in deep coal mine roadways - Huan Zhang; Min Zhang; Zhunli Tan; Jianzhong He; Wenbo Yu; Xiaomin Zhao (Journal of Materials Research and Technology)
Steel rebars with excellent strength and toughness are considered promising construction materials used in deep coal mine roadways. However, the harsh and complex loading conditions in deep mining often leads to damage and failure of support structures. In this work, we propose an effective strategy to address these challenges by designing a heterogeneous microstructure into steel rebars to tune mechanical behaviors via varying intercritical quenching temperatures. This process not only leads to a heterogeneous microstructure containing ferrite and granular structure with different phase fractions but also promotes the precipitation of abundant nanosized V-precipitates, contributing to microstructure refinement. The heterogeneous microstructure was thoroughly characterized by OM, SEM, XRD, TEM and EBSD, while its mechanical properties were investigated through tensile tests and Charpy impact tests. Results show that as the intercritical quenching temperature increases from 750 to 830 °C, lower bainite is gradually replaced by granular structure, ferrite volume fraction decreases and lath martensite disappears completely, while retained austenite volume fraction is the highest at 800 °C. The heterostructure influences overall strength fluctuation through dislocation strengthening, and effectively improves both impact toughness and plasticity collectively attributed to higher retained austenite and variant selection. 700 MPa bainitic steel rebars with excellent mechanical properties (YS > 730 MPa, UTS >1100 MPa, E > 25% and Akv > 43 J) can be obtained with a yield ratio of 0.66. This study presents a hierarchical microstructure design for developing high-performance steel rebars, offering an effective avenue to the long-standing conflicts between strength and toughness.